ISLAMIC BOARDING SCHOOL OF MIFTAHUL MIDAD LUMAJANG IN THE PROCESS TOWARDS MODERN EDUCATION CENTER - Mahmawati, Diyah; Novitaningrum, Angella; Mas’ud, Mohammad; Yuswandari, Kurnia Devi; Wisnu, Wisnu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This article wants to reveal the development of the Islamic Boarding School of Miftahul Midad Lumajang in the process of going global. Miftahul Midad Lumajang meets the criteria of a modern Islamic Boarding School and has formatted its curriculum into an Islamic education model that is acceptable to various groups. Since its establishment in the 1980s, its development has been very rapid, because it not only implements the salaf system but also uses the integrated curriculum of the Ministry of Religion's formal school format. Now, after the opening of the institution, several surges of concept developments are put into practice. The theme of this article's discussion is how the implementation of the khalaf salaf curriculum in formal education at the Islamic boarding school of Miftahul Midad Lumajang is in facing the challenges of the times. Some of the problems are also how caregivers adopt the khalaf salaf curriculum with the opening of MTs, MA, and institutions. The ranks of caregivers provide evidence of success in practicing the khalaf salaf curriculum in the implementation of side-by-side learning. This success comes from the quality of the students and the ability of caregivers and teachers to coordinate to guide the students.